The Effect of The Application of Business Model Resources and Digital Innovation on Business Models and Innovation Capacity on the Performance of Micro, Small, and Medium Enterprises of Jewelry Shops in Blora and Grobogan Regencies During the Covid-19 Pan - Wijaya, Alim; Christian Efrata, Tommy (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
This study analyzes the effect of implementing business model resources, digital innovation activities, business models, and innovation capacity on low-middle enterprise performance. The background of the research is due to the Covid-19 pandemic, which has caused a decrease in the number of low-middle enterprises accompanied by the digital disruption that makes people habitually move online. A pandemic and digital disruption have forced low-middle enterprise business owners in jewelry shops, especially Blora Regency and Grobogan Regency, to implement digital innovation into their business models to improve company performance. However, many business owners have not implemented digitalization because they are not fully willing to allocate funds for business model resources and innovation practices—the quantitative method with data collection tools in the form of a Likert scale questionnaire. The sample used is a jewelry shop located in Blora Regency and Grobogan Regency with several criteria. The number of samples was calculated by the Hair formula. The variables used in this research are Business Model Resources (X1), Digital Innovation Activities (X2), Business Model (X3), Innovation Capacity (X4), and Company Performance (X5). Data analysis using SEM method with the help of SmartPLS 3.0 software. The study results show a significant relationship between variables except for the Digital Innovation Activity (X2) and Business Model (X3) variables because digital innovation activities lack a competitive advantage against market needs.